Barriers to follow-up after an abnormal cervical cancer screening result and the role of male partners: a qualitative study - Mercy Tsidya; Lameck Chinula; Jennifer H Tang; Clement Mapanje; John Chapola; Fan Lee; Agatha Bula; Billy Rodwell Phiri; Nenani Kamtuwange (BMJ Open)
Introduction Cervical cancer is the leading cause of cancer deaths among women in Malawi, but preventable through screening. Malawi primarily uses visual inspection with acetic acid (VIA) for screening, however, a follow-up for positive screening results remains a major barrier, in rural areas. We interviewed women who underwent a community-based screen-and-treat campaign that offered same-day treatment with thermocoagulation, a heat-based ablative procedure for VIA-positive lesions, to understand the barriers in accessing post-treatment follow-up and the role of male partners in contributing to, or overcoming these barriers.Methods We conducted in-depths interviews with 17 women recruited in a pilot study that evaluated the safety and acceptability of community-based screen-and-treat programme using VIA and thermocoagulation for cervical cancer prevention in rural Lilongwe, Malawi. Ten of the women interviewed presented for post-treatment follow-up at the healthcare facility and seven did not. The interviews were analysed for thematic content surrounding barriers for attending for follow-up and role of male partners in screening.Results Transportation was identified as a major barrier to post-thermocoagulation follow-up appointment, given long distances to the healthcare facility. Male partners were perceived as both a barrier for some, that is, not supportive of 6-week post-thermocoagulation abstinence recommendation, and as an important source of support for others, that is, encouraging follow-up attendance, providing emotional support to maintaining post-treatment abstinence and as a resource in overcoming transportation barriers. Regardless, the majority of women desired more male partner involvement in cervical cancer screening.Conclusion Despite access to same-day treatment, long travel distances to health facilities for post-treatment follow-up visits remained a major barrier for women in rural Lilongwe. Male partners were identified both as a barrier to, and an important source of support for accessing and completing the screen-and-treat programme. To successfully eliminate cervical cancer in Malawi, it is imperative to understand the day-to-day barriers women face in accessing preventative care.